(untitled) (Perner’s Contacts, 2008)
Contents of contribution is implementation ones of subsystem of integrated transport system for use Prešov in city and urban traffic. The contribution describes possible computer – aided design of programm AutoCAD 2008 for harmonization of traffic process.